Epidemiology of Polypodium hydriforme in American Paddlefish. Issue 9 (6th July 2020) - Okamura, Beth; Hartigan, Ashlie; Long, Paul F.; Ruggeri, Paolo; Smith‐Easter, Katie; Schooley, Jason D.
Abstract: Polypodium hydriforme is a parasitic cnidarian that develops within the eggs of acipenseriform fish in the Old and New Worlds. Currently regarded as monotypic, P. hydriforme has been studied largely in the context of caviar production in Russian sturgeon species. We report the first robust epidemiological study of P. hydriforme in North American acipenseriform fish. We sampled infection prevalences (in 2017 and 2018) and intensities (in 2017) during annual surveys of American Paddlefish, Polyodon spathula, caught during spawning migration in north‐eastern Oklahoma. Egg masses were characterized for the presence and intensity of P. hydriforme infection. Prevalences were similar in 2017 and 2018 (49% and 45%, respectively). Generally, a small number of eggs were infected per egg mass, but a few were heavily infected. Longer, heavier and older fish are more likely to be infected and to harbour more severe infections. In addition, infection is linked to decreases in roe fat weight independently of fish length, weight, age or roe weight. Infection thus diminishes Paddlefish energy reserves (roe fat) which could in turn impact host fitness. Our results raise questions about the impacts of infection on caviar production and Paddlefish conservation and suggest insights on infection dynamics and parasite strategies.